LncRNAs divide and rule: The master regulators of phase separation - Somasundaram, Kumaravel; Gupta, Bhavana; Jain, Nishkarsh; Jana, Samarjit (Frontiers in Genetics, 2022)
Most of the human genome, except for a small region that transcribes protein-coding RNAs, was considered junk. With the advent of RNA sequencing technology, we know that much of the genome codes for RNAs with no protein-coding potential. Long non-coding RNAs (lncRNAs) that form a significant proportion are dynamically expressed and play diverse roles in physiological and pathological processes. Precise spatiotemporal control of their expression is essential to carry out various biochemical reactions inside the cell. Intracellular organelles with membrane-bound compartments are known for creating an independent internal environment for carrying out specific functions. The formation of membrane-free ribonucleoprotein condensates resulting in intracellular compartments is documented in recent times to execute specialized tasks such as DNA replication and repair, chromatin remodeling, transcription, and mRNA splicing. These liquid compartments, called membrane-less organelles (MLOs), are formed by liquid-liquid phase separation (LLPS), partitioning a specific set of macromolecules selectively from others. While RNA binding proteins (RBPs) with low complexity regions (LCRs) appear to play an essential role in this process, the role of RNAs is not well understood. It appears that short nonspecific RNAs keep the RBPs in a soluble state, while longer RNAs with unique secondary structures promote LLPS formation by specifically binding to RBPs. This review will update the current understanding of phase separation, physio-chemical nature and composition of condensates, regulation of phase separation, the role of lncRNA in the phase separation process, and the relevance to cancer development and progression.